2015
DOI: 10.1093/intimm/dxv031
|View full text |Cite
|
Sign up to set email alerts
|

Common marmoset CD117 + hematopoietic cells possess multipotency

Abstract: Analysis of the hematopoiesis of non-human primates is important to clarify the evolution of primate-specific hematopoiesis and immune regulation. However, the engraftment and development of the primate hematopoietic system are well-documented only in humans and are not clear in non-human primates. Callithrix jacchus (common marmoset, CM) is a New World monkey with a high rate of pregnancy and small size that lives in closed colonies. As stem cell factor (SCF) is an essential molecule for hematopoietic stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Even concomitant PI3K and Bcl-2/Bcl-X L inhibition suppresses tumor growth and enhances survival of NOD/SCID-gamma mice in vivo using a U937 cell xenograft model [35]. In immunodeficient NOG mice, xenografted common marmoset CD117 + hematopoietic cells can be differentiated into lymphocytes [36]. Furthermore, many experiments have shown that caspases are activated when apoptosis is induced by other factors, such as the potent antitumor drug doxorubicin [37] and TNF-α [38].…”
Section: Discussionmentioning
confidence: 99%
“…Even concomitant PI3K and Bcl-2/Bcl-X L inhibition suppresses tumor growth and enhances survival of NOD/SCID-gamma mice in vivo using a U937 cell xenograft model [35]. In immunodeficient NOG mice, xenografted common marmoset CD117 + hematopoietic cells can be differentiated into lymphocytes [36]. Furthermore, many experiments have shown that caspases are activated when apoptosis is induced by other factors, such as the potent antitumor drug doxorubicin [37] and TNF-α [38].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with these results, Izawa et al . (2004) [ 29 ] and our group (2008) [ 78 ] observed the multilineage differentiation of CD34+ cells in NOD/SCID and NOG mice. Schrimpf et al .…”
Section: Differentiation Of Immune Cellsmentioning
confidence: 99%
“…Therefore, we established an anti-CM CD34 monoclonal antibody and anti-CM CD117 monoclonal antibody, and identified CD117 as a CM HSC marker using these antibodies [ 29 , 33 ]. Next, we examined if the multipotency and developmental pathway of CM HSCs were similar to those of humans by transplanting the cells into severely immunodeficient NOG mice [ 27 , 55 , 78 ]. CM bone mallow cells were collected from newborn CMs that were abandoned due to a birth of triplets.…”
Section: Differentiation Of Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations